Land use and land cover change and system level analysis to guide sustainable intensification efforts in mixed crop-livestock farming system - Tesfaye, Getachew; Tibebe, Degefie; Abera, Wuletawu; Tamene, Lulseged D. (2024)
Changes in land use and land cover (LULC) are a major concern in Ethiopia. It has a significant impact on the environment, food and feed availability, and other ecosystem services and products for present and future generations. The effects of LULC change are particularly more pronounced in the highlands of Ethiopia, where the majority of the country’s cultivated land and livestock grazing occur, and competition between different land use decisions is a major concern. As a result, analysing spatial and temporal LULC changes and determining their primary causes is crucial for implementing effective land use planning, intervention targeting, and scaling out. The aim of this study was to analyse recent LULC changes in Basona Worena Woreda between 2013 and 2022 and identify the key drivers of change and their implications in the study area. The analysis was performed using Landsat 8 satellite imagery and random forest classification algorithms in the Google Earth Engine environment. Accordingly, agricultural land was identified as the dominant LULC type in the study area. It currently covers more than half of the total study area. Agricultural lands have expanded significantly, increasing from 42.3% in 2013 to 66.5% in 2022. Forest land and grassland, on the other hand, decreased from 30.3% and 21.2% in 2013 to 13.7% and 8.2% in 2022, respectively. Bareland coverage has expanded from 5% in 2013 to 9.3% in 2022. Thus, between 2013 and 2022, agricultural land and bareland have a net gain of 301.6 and 53.3 km2, respectively, whereas forestland and grassland have a net loss of 206.1 and 162 km2, respectively. The analysis has further indicated that a significant portion of the study areas (466 km2 or 37%) has experienced some form of LULC changes between the study periods. Between 2013 and 2022, 393.1 km2 of land from other LULC types were converted to agriculture, accounting for 31.5% of the total study area. The transition from forest and grassland to agricultural land constitutes the lion’s share of this, taking up 187.9 KM2 (48%) and 158 Km2(40%), respectively, of the total changes. A considerable portion of bareland has also been converted to agricultural land, accounting for 39.8 KM2 or 10% of the total changes. Agricultural land, grassland, and forest land (101 KM2 or 8% of the total study area) was turned into bareland. A total of 40 KM2 of forestland was also converted to grassland. In contrast, a considerable amount of land, primarily from grasslands and agricultural lands, was converted to forestlands. Rapid population growth, land scarcity, low productivity, poverty, poor agricultural and grassland management practice, and other factors have been recognized as important drivers of LULC change in Ethiopia’s highlands. With the business-as-usual scenario, the expansion of agricultural land and land degradation concerns caused by the conversion of LULC types will likely worsen. Thus, expansion of agricultural land and land degradation are the most critical and ongoing concerns of the study area that must be addressed if future land use systems are to continue delivering the necessary food, feed, and other ecosystem services sustainably. Thus, system level sustainable interventions are suggested as a way maintaining the ecosystem balance and halt the expansion of agriculture and land degradation in the study area.